Mentality Readiness, Morality, and Work Ethic in the Industrial World: A Counseling Program at SMK Fatahillah 1 Cilegon - Tatang Mahpudin; Titis Sri Wulan; Silvia Rachmadani; Muhammad Rizki Ashari; Siti May Khofifa (PT. Global Research Collaboration, 2026)
Mental, moral, and work ethic readiness are important foundations that Vocational High School (SMK) students must have in facing the demands of an increasingly competitive industrial world. These three aspects not only support technical skills, but also determine students' success in adapting to real work dynamics. A strong mentality helps students face the pressures and challenges of industry, good morality forms integrity and responsibility in work, while a strong work ethic encourages discipline, productivity, and professionalism. Based on this urgency, the community service team carried out counseling activities at SMK Fatahillah 1 Cilegon with the theme